3d-Metal-Catalyzed Single-Electron-Transfer-Induced Conversion of Carboxylic Acids and Their Equivalents - Shinde, Rupali Dasharath; Patel, Upendra Kumar Brijmohan; Bhadra, Sukalyan (Synlett, 2024)
This account describes the latest developments on 3d-metal-catalyzed single-electron-transfer (SET)-induced strategies that use carboxylic acids and their synthetic equivalents as substrates. In general, 3d-metal-promoted SET-mediated transformations of free carboxylic acids proceed readily via the formation of carboxylate radicals, whilst those of carboxylic acid equivalents, bearing an N-donor substituent, proceed via the formation of α-carbo radicals. The advantages of these strategies combine the low-cost of carboxylic acid starting materials and 3d metal catalysts with the possibility of realizing structurally diverse ranges of compounds in an atom- and step-economic manner. Developments primarily achieved by our group and a few by other researchers on this topic are discussed in this account.1 Introduction2 Mechanistic Considerations of 3d-Metal-Catalyzed SET-Mediated Transformations3 Developments Based on SET-Mediated Transformations of Carboxylic Acids4 Developments Based on SET-Mediated Transformations of Carboxylic Acid Equivalents5 Conclusion and Outlook
Keywords: carboxylic acid; single-electron transfer; radical reactions; copper; iron; cobalt